Nove najdbe redke vrste Pretneria metkae Bognolo, 2000 (Coleoptera: Cholevidae: Leptodirinae) - Kofler, Bojan (Acta entomologica slovenica (Ljubljana), 2020)
Pretneria metkae, a rare species, was found in 4 locations on the Mt. Triglav (2863m): Ivačičeva jama (Cad. No.:2399), Snežna konta under Mali Triglav, Kotel under north face of Kredarica and on the path between Dom Planika and Triglavska škrbina.
Keywords: beetles; Cholevidae; Coleoptera; fauna; favna; Hrošči; Leptodirinae; Pretneria; Pretneria metkae; Slovenia; Slovenija; Žuželke